Blue, Green and Yellow Emissions at the Same Time from Mn-doped ZnS Microbelts - Nguyen Van, Nghia (VNU Journal of Science: Mathematics - Physics; Vol 34 No 1DO - 10.25073/2588-1124/vnumap.4212, 2018)
We present an investigation of the morphology, structure, composition and optical properties of ZnS:Mn 2+ microbelts grown by the thermal evaporation method using ZnS powder and MnCl 2 .4H 2 O powder as precursor materials. The SEM images of the products show that ZnS:Mn 2+ microbelts are bigger and shorter than ZnS microbelts. EDS reveals that the composition of the microbelts include Zn, S, O, Mn and Cl elements. The atom rate of oxygen composition of the doped microbelts seem to be slightly lower than undoped ones. XRD pattern of the prepared microbelts shows that ZnO coexists with ZnS on the undoped microbelts. However, at the Mn-doped microbelts, the component phase of ZnO is disappeared. Photoluminescence spectra of undoped ZnS microbelts reveal a strong broad emission band at visible wavelength region and a weak ultraviolet band. Interestingly, when Mn 2+ is doped into the microbelts, the visible emission band is separated into blue, green, and yellow bands peaking at around 442, 520 nm, and 572 nm, respectively. The effects of Mn 2+ ions on the emission bands is discussed in detail.